Customers’ confidence and trust towards privacy policy: a conceptual research of hotel revenue management - Michael, Tinggi; Shaharudin, Jakpar; Ting, Bick Chin (Inderscience Enterprises Ltd., 2011)
This empirical research involves determination on customers’ confidence on hotel’s custodian of customers’ personal information as Kao et al. (2008) suggests that increase customers’ confidence may enhance customers’ satisfaction experiential value and may imply revenue potential. Customers demand assurance that their personal data will be safe and secure. A confident and satisfied customer may spread favourable words of mouth about hotel privy image that will eventually bring about positive impact on revenue. Seventy randomly selected respondents were interviewed and distributed with closed structured questionnaire to investigate some chosen antecedents’ variables, a determinant construct of customers’ confidence and trust. The findings corroborate that customers’ personal belief primarily contributes to their high level of confidence on hotel privacy policy. Therefore, in an effort to achieve a potential revenue management, the hoteliers have to be mindful of customers’ belief, as a major driver for consumers enhanced confidence.